Current usage by a DC motor to vary ratio in an electro-mechanical continuously variable transmission. Issue 1 (July 2020) - Delhaise, L J; Mazali, I I; Daud, Z H C; Kob, M S C; Asus, Z
Abstract: In a typical continuously variable transmission (CVT) for automotive, engine torque is transmitted from the primary pulley (connected to the vehicle's engine) to the secondary pulley (connected to the wheels) through a metal pushing V-belt. The CVT ratio ( rCVT ) is defined as the pitch radius of the belt on the secondary pulley divided by the pitch radius on the primary pulley. Conventionally, rCVT is varied using hydraulic pressure generated by an oil pump which is powered by the engine. A continuous hydraulic pressure is required to maintain high clamping force applied on the belt so that sufficient traction between the belt and the pulleys can always be provided. This requirement, unfortunately, causes significant power losses in the CVT and to address this, the idea of electro-mechanical CVT (EM CVT) is proposed. In an EM CVT, rCVT is varied using a power screw mechanism and a DC motor while the desired ratio and the belt's clamping force is maintained using the thread of the power screw mechanism, consequently eliminating the aforementioned issue. This paper describes the process of measuring the current used by a DC motor to vary rCVT in an EM CVT. The results show that the current usage is higher during upshifting from rCVT of 1.95 to 1.43 (about 45 A) as compared to downshifting from 1.43 to 1.95 (about 23 A). This is due to the application of disc springs in the secondary pulley that reduces the required motor torque for downshifting. The results also prove that no current is consumed by the motor during a constant rCVT . In conclusion, the motor's current usage has been successfully measured and the results can be used for a future development of the EM CVT's battery system.